FISCAL POLICY AND ITS ROLE IN ADDRESSING UNEMPLOYMENT IN IRAQ (2010-2020) - Sabah Ahmed Asmaeel (Jurnal Ekonomi, Bisnis dan Pendidikan, 2026)
Unemployment is one of the most serious economic and social problems facing the Iraqi economy. At the time unemployment in Iraq worsened significantly after 2010 due to political and security changes, compounded by the rentier structure of the oil-dependent economy. This research aims to analyze the role of fiscal policy, through its instruments of government spending, tax revenues, and public debt, in addressing unemployment in Iraq during the period 2010-2020. The research employed a descriptive-analytical approach, utilizing data from the Central Bank of Iraq and the Ministry of Planning. The study found an economic relationship between fiscal policy and unemployment; however, this relationship was not sufficiently effective due to the dominance of consumer spending over investment spending, weak tax revenues, and fluctuating oil prices, which negatively impacted financial stability. The research recommends restructuring government spending to favor investment, diversifying revenue sources, and supporting the private sector and labor-intensive sectors such as agriculture and tourism.